Thione-thiol tautomerism of thiourea ligands on silica surface - O. V. Smirnova; A. G. Grebenyuk; G. I. Nazarchuk; Yu. L. Zub (Хімія, фізика та технологія поверхні)
Quantum chemical calculations of the IR spectra of the thione and thiol forms of N, N'-dimethylthiourea and silica surface fragment with composition (HO)3SiCH2NHC(S)NHCH3 (density functional theory method, B3LYP/6-31G (d, p)) make it possible to fix indicator absorption bands of the tautomers. The presence of absorption bands at 1586 cm-1 (or 1607 cm-1 in the case of surface fragment) reveals the thione form whereas appearance of the intensive absorption bands at 1714 (1707)cm -1 indicates the occurrence of the thiol form. The results of quantum chemical calculations on the total energy of the transition complex in vacuum at T = 298 K and on the activation energy values of thione-thiol tautomeric transition between different conformations of the cluster models have shown a decrease in the activation barrier due to the grafting of thiourea groups on silica surface. The configurations of the transition complexes were also determined.